Jane Jacobs, a Rebel with a Cause - Jan Steyaert (Social Work & Society, 2012)
It is more than five years now since Jane Jacobs died in Toronto, having nearly reached the age of 90. Her name still resonates powerfully and most likely will do for several years and decades to come. Her life was a fascinating one and her thoughts on urban life have been highly influential across the world. Although the major social work journals contain few references to her work, her key concepts have rightly influenced social work practice. This article tries to rectify the absence of her work in scholarly social work journals and to honour Jane Jacobs as a rebel with a cause.